2023
DOI: 10.1002/advs.202206713
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation of Candida albicans Sap2 Enhances Fungal Pathogenicity via Complement Evasion and Macrophage M2‐Like Phenotype Induction

Abstract: Candida albicans (C. albicans) is an opportunistic pathogen increasingly causing candidiasis worldwide. This study aims to investigate the pattern of systemic immune responses triggered by C. albicans with disease associated variation of Sap2, identifying the novel evasion strategies utilized by clinical isolates. Specifically, a variation in clinical isolates is identified at nucleotide position 817 (G to T). This homozygous variation causes the 273rd amino acid exchange from valine to leucine, close to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The highest activity affecting biofilm stability was demonstrated by Sap2, Sap9, and Sap10. Sap2 is the major aspartic proteinase of broad substrate specificity and is secreted extracellularly by C. albicans, being involved in nutrient acquisition and associated with fungal virulence-host invasion, tissue damage, and immune evasion [27,56,57]. Although the optimum activity of Sap2 is at acidic pH, research presented by Lin et al [57] showed that this proteinase might also be active at pH 7.…”
Section: Discussionmentioning
confidence: 99%
“…The highest activity affecting biofilm stability was demonstrated by Sap2, Sap9, and Sap10. Sap2 is the major aspartic proteinase of broad substrate specificity and is secreted extracellularly by C. albicans, being involved in nutrient acquisition and associated with fungal virulence-host invasion, tissue damage, and immune evasion [27,56,57]. Although the optimum activity of Sap2 is at acidic pH, research presented by Lin et al [57] showed that this proteinase might also be active at pH 7.…”
Section: Discussionmentioning
confidence: 99%
“…As for C. parapsilosis, Sapp2 exhibits a quite narrow substrate specificity and lower catalytic activity than Sapp1 [47]. Moreover, in the case of C. albicans Saps, pH within the range of 3.0-5.0 was indicated as optimal for their proteolytic activity [44]; however, these enzymes are also active at a pH close to neutral, which significantly expands their potential range of action [44,48]. C. tropicalis Sapt2 and Sapt3 had a pH optimum of 5.0, while the optimal pH for Sapt1 activity was assigned to 3.5 [24].…”
Section: Candida Pathogenic Yeasts-their Clinical Relevance As Opport...mentioning
confidence: 99%
“…Additionally, Sap2 can also interfere with CR3 and CR4 receptor expression in macrophages [138]. Recently, clinical isolates of C. albicans have been analyzed that displayed a new strategy to evade the host immune system [48]. The exchange of the amino acid at position 273 in Sap2 from valine to leucine resulted in escalated proteolytic activity of Sap2273L compared to Sap2273V, suggesting an increased ability of C. albicans to evade the complement response and, consequently, an increase in pathogenicity [48].…”
Section: Proteolysis Of Complement Antibodies and Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions are characterized by systemic dysregulation of inflammatory and excessive immune responses [ 1 , 2 ]. Immunotherapy based on suppression of pro-inflammatory peripheral immune cells (neutrophils, macrophages and T lymphocytes) has been proven effective in various treatments of inflammatory diseases [ 3 , 4 ]. Tolerant dendritic cells (DC) play a critical role in immune suppression therapy [ 5 ] through various mechanisms, including depletion of auto-reactive T cells [ 6 ], promotion of regulatory T cells (Treg) [ 7 , 8 ] and expression of inhibitory molecules [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%